Pengaruh Self Management Hipertensi Berbasis Website Pada Ibu Hamil Di Puskesmas Masamba - Nur Pitasari; A. Muhammad Multazam; Masriadi (Window of Public Health Journal, 2025)
Hypertension is an incurable disease; the use of antihypertensive drugs and lifestyle changes can prevent the disease from occurring. Hypertension in pregnancy is defined as a systolic blood pressure greater than 140 mmHg and a diastolic blood pressure greater than 90 mmHg. High maternal blood pressure (hypertension) can cause intrauterine fetal growth disorders, which will undoubtedly impact birth weight. Hypertension in pregnancy is a vascular disorder that occurs before pregnancy or arises during pregnancy or at the beginning of the postpartum period. This study aims to determine the effect of self-management interventions on the incidence of hypertension in pregnant women before and after implementation at the Masamba Community Health Center, Masamba District, North Luwu Regency (web-based). This study employs a quantitative approach with a quasi-experimental design featuring a control group and a pretest-posttest design. The study sample consisted of 30 people (from both the control and intervention groups), selected using a non-probability sampling method. Data collection utilized a website that contained questionnaires and intervention materials. Data analysis used a paired t-test with a significance level of α = 0.05. The results of this study indicate that the self-regulation pretest–post–test of the intervention group (0.000), while the pretest–post–test of the control group (0.420), and the interaction variable with health workers pretest–post–test of the intervention group (0.000), while the pretest – post-test of the control group (0.869). Based on the results of this study, it can be concluded that a website-based self-management intervention influences the incidence of hypertension in pregnant women before and after its implementation at the Masamba Community Health Center, Masamba District, North Luwu Regency.